Mobility variation of a family of metamorphic parallel mechanisms with reconfigurable hybrid limbs. (October 2016) - Ye, Wei; Fang, Yuefa; Zhang, Ketao; Guo, Sheng
Abstract: This paper presents a planar metamorphic mechanism (PMM) which has three distinct working phases and a family of metamorphic parallel mechanisms with a PMM as closed-loop subchain in each limb. The study starts from analysis of mobility variation and motion characteristics in each phase of the PMM based on screw theory. Three types of reconfigurable hybrid limbs are then constructed by integrating the PMM and serial chains capable of supplying one constraint force and one constraint couple. This leads to the design of a new family of metamorphic parallel mechanisms in which the platform is connected to the base by three reconfigurable hybrid limbs. The configuration changes of the reconfigurable limb associate with the three distinct phases of the PMM are analyzed and the constraints exerted by the reconfigurable limb in various configurations are identified. The analyses reveal that the metamorphic parallel mechanisms have ability to alter the performance of platform from full 6-DOF configuration to 5-, 4- and 3-DOF configurations resorting to the internal configuration variation of the three reconfigurable limbs. Finally, actuation models with selected joints for mounting drives for the metamorphic parallel mechanisms are addressed and application cases including the potential for hybrid additive and subtractive manufacturing machine of the proposed mechanisms are discussed in details. Highlights: A planar metamorphic mechanism with three working phases is proposed. Three types of hybrid reconfigurable limbs are constructed. A family of metamorphic parallel mechanisms is obtained. The metamorphic parallel mechanisms have ability to alter the performance of platform from full 6-DOF to 3-DOF. Six motors near to the base are efficient for each mechanism.